Effect of the pulsed electromagnetic field in the repair of a calvaria critical bone defect in rats: cone beam computed tomographic and histomorphometric analysis.: PEMF in the repair of a calvaria critical bone defect: CBCT analyses. - Moura, Nicole Bertonde [UNESP]; Ferreira, Camila Lopes [UNESP]; Lima, Victória Clarada Silva [UNESP]; Nunes, Camilla Magnoni Moretto [UNESP]; de Marco, Andrea Carvalho [UNESP]; Costa, André Luiz Ferreira; Lopes, Sérgio Lúcio Pereirade Castro [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (Elsevier, 2023)
Introduction: The present study evaluated the effect of two protocols of Pulsed Electromagnetic Field (PEMF) therapy on bone neoformation on calvaria critical defects in rats. Material & methods: 96 rats were randomly divided into 3 groups: Control Group (CG; n=32); Test Group – PEMF 1 hour (TG1h; n=32) and Test Group – PEMF 3 hour (TG3h; n=32). A Critical-size Bone Defect (CSD) was surgically created in the calvaria of rats. The animals in the test groups were exposure to PEMF for 5 days a week. The animals were euthanized at 14, 21, 45 and 60 days. The specimens were processed for volume and texture (TAn) analysis, by Cone Beam Computed Tomography (CBCT) and histomorphometric analysis, Results: Histomorphometric and volume analyses revealed that there was no statistically significant difference in the repair of bone defects between groups receiving PEMF therapy and CG. TAn revealed a statistically significant difference between the groups only for the entropy parameter, in which TG1h group presented a higher value compared to CG on 21 days. TG1h and TG3h did not accelerate bone repair in calvarial critical size defect and the parameters of PEMF should be considered. Discussion: This study showed that PEMF application on CSD in rats does not accelerate bone repair. Although literature showed a positive association in biostimulation on bone tissue with the parameters applied, studies with other PEMF parameters are essential to verify improving this study design.
Keywords: Bone regeneration; Cone beam computed tomography; Electromagnetic fields